Radiation protection and structural performance of PVDF composites reinforced with lead zirconate titanate nanoparticles: A smart shield - Altun, Sedanur; Yılmaz, Demet; Doğan Ulu, Öznur; Selçuk Pekdemir, Sibel; Ulu, Ahmet; Pekdemir, Mustafa Ersin; Ateş, Burhan (Elsevier Ltd, 2026)
Polyvinylidene fluoride (PVDF) is a widely utilized polymer known for its excellent flexibility, notable thermal stability, and strong resistance to chemical degradation, which make it suitable for advanced engineering applications. Lead zirconate titanate (PZT), on the other hand, is a perovskite-type ferroelectric ceramic composed of lead, zirconium, and titanium oxides, offering significant potential for improving radiation shielding performance. In the present work, PVDF composites reinforced with PZT nanoparticles (1%, 2%, 4% and 8% (w/v)) were prepared to achieve lightweight and flexible materials with enhanced radiation shielding capability. Structural and thermal properties were characterized using ATR-IR, XRD, SEM, and TGA/DSC analyses. ATR-IR spectra confirmed the retention of PVDF's chemical structure, while XRD results indicated the coexistence of PVDF and PZT phases with improved crystallinity at intermediate filler levels. Thermal analysis demonstrated the residual weights of the composite films containing 1%, 2%, 4%, and 8% PZT were determined to be 0.63%, 0.97%, 2.35%, and 5.80%, respectively. These outcomes revealed that increased residual weight and slight improvement in thermal stability with higher ceramic loading, attributed to the non-volatile nature of PZT. Moreover, the radiation attenuation performance was investigated for photons in the energy range of 13.37–59.54 keV with a variable-energy X-ray source and ULEGe detector. The macroscopic cross sections were calculated for neutrons at thermal (25.4 meV) and fast (4 MeV) energies. The addition of PZT significantly improved gamma shielding efficiency; for instance, the half-value layer decreased from 0.727 cm for neat PVDF to 0.409 cm at 24.5 keV, accompanied by an increase in effective atomic number. Thermal neutron macroscopic cross-sections slightly declined due to reduced hydrogen content, whereas fast neutron and removal cross-sections showed only minor changes despite increased density and lead content. These results indicated that PVDF/PZT composites combine structural stability and thermal resistance. The use of PZT also provides potential multifunctionality, especially in medical and nuclear environments where flexibility and weight reduction, radiation protection, piezoelectric properties are essential. © 2026 Elsevier Ltd.
Keywords: Neutron shielding; polymer composite; PVDF; PZT; Radiation shielding